2017
DOI: 10.1038/bjc.2017.142
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti-PD-1 therapy in patients with melanoma brain metastases

Abstract: Background:There is limited data on the efficacy of anti-programmed death 1 (PD-1) antibodies in patients (pts) with melanoma brain metastasis (BM), particularly those which are symptomatic.Method:We retrospectively assessed pts with melanoma BM treated with PD-1 antibodies, nivolumab and pembrolizumab. Clinicopathologic and treatment parameters were collected and outcomes determined for intracranial (IC) response rate (RR) using a modified RECIST criteria, with up to five IC target lesions used to determine I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 34 publications
3
57
0
1
Order By: Relevance
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 81%
See 1 more Smart Citation
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 81%
“…A handful of retrospective and prospective clinical studies indicated activity of ipilimumab in melanoma BrM with 16-25% intracranial response rate, but also suggested that only a subgroup of patients is likely to benefit (4,5,11). Pembrolizumab and nivolumab also showed efficacy in melanoma BrM with an ~21% response rate in the brain (12)(13)(14)(15). A very recent interim analyses from two clinical trials in drug-treatment naïve patients with melanoma BrM (ABC trial (15) and CheckMate 204 trial (16)) reported a 50% and 55%…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown in a retrospective trial that nivolumab treatment in patients with MBM leads to a median overall survival of 9.9 months. Similar to the results with ipilimumab, patients who are corticosteroid independent and with asymptomatic MBM had a better progression‐free survival and median overall survival . A retrospective analysis of RT for MBM in a patient population treated with nivolumab has shown a good local and distant control and a median overall survival of about 12 months.…”
Section: Discussionsupporting
confidence: 61%
“…Similar to the results with ipilimumab, patients who are corticosteroid independent and with asymptomatic MBM had a better progressionfree survival and median overall survival. 42 A retrospective analysis of RT for MBM in a patient population treated with nivolumab has shown a good local and distant control and a median overall survival of about 12 months. Similar to the studies with ipilimumab, the performance status was predictive of a good overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the use of corticosteroid, an immunosuppressive agent, particularly in patients with brain metastasis or glioblastoma, has been associated with poor outcome after immunotherapy. Keskin and colleagues demonstrated that patients with glioblastoma who received dexamethasone during administration of personalized neoantigen vaccines were unable to generate neoantigen‐specific CD4+ and CD8+ responses in both peripheral blood and the TME.…”
Section: Safety and Feasibility Of Surgery In Patients On Immunotherapymentioning
confidence: 99%